Penggunaan Model Pembelajaran Problem Based Learning dalam Meningkatkan Hasil Belajar Siswa Geografi di Negeri 1 Tombulu - Kindangen, Yosua Yeremia; Kaihatu, Jolanda Esther; Oroh, Hilda Vemy; Tewal, Selvana Treny Rosita; Sindua, Nixon Jefres; Sumilat, Grystin Djein (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in enhancing geography learning outcomes among students at SMA Negeri 1 Tombulu, using a quantitative approach with a pre-experimental design (One Group Pretest-Posttest). The sample was selected through purposive sampling from the population of class XI Social Studies. Data collection employed triangulated instruments: motivation questionnaires, grade documentation, and participatory observation. Descriptive analysis revealed a significant increase in mean scores from pretest (56.66) to posttest (80), with 83.33% of participants (5 students) achieving the Minimum Completeness Criteria (KKM) in the final phase, compared to none initially. These findings underscore the pivotal role of PBL in optimizing conceptual assimilation of global-local flora and fauna distribution through inquiry-based learning and collaborative group mechanisms. Pedagogically, the study recommends integrating PBL as an alternative strategy within geography curricula to strengthen cognitive and analytical skills.